Building the next generation groupware: A survey of groupware and its impact on the virtual enterprise - Terzis, Sotirios; Nixon, Patrick (Trinity College Dublin, Department of Computer Science, 1999)
[Executive Summary] This document explores the issues in building the ?groupware of the future?. The approach is twofold. First we briefly describe our vision of a ?virtual enterprise? that is made up of a set of services through a composition of components that comply with a specific contract (specification). Two scenarios are presented which demonstrate the set of underlying requirements. Secondly, a review of the-state-ofthe- art in groupware technology is presented which identifies a set of services provided by current groupware systems. An assessment of the relative importance of these services is then presented and a comparison made to the requirements specified in the part one. A more detailed presentation of a subset of ?important? groupware projects or products clarifies the limitations of current approaches. These limitations, in conjunction to the current trends in software technology (object technology, component architectures, web technology etc), determine the next steps towards our vision. The document concludes with a presentation of our definition for the ?groupware of the future? and the route towards it.
Keywords: Computer Science